Marginal and joint failure importance for K-terminal network edges under counting process. (July 2022) - Ma, Chengye; Du, Yongjun; Zhang, Yuchun; Cai, Zhiqiang
Highlights: The MFI is derived when network edge failures are subject to a counting process. The JFI is derived when network edge failures are subject to a counting process The Monte Carlo method-based algorithm is devised to calculate the MFI and JFI. The values of edge importance are discussed for a road network with saturated NHPP. ABSTRACT: Importance measures have been applied extensively in various fields such as reliability optimization, failure diagnosis, and risk analysis. Traditional importance measures are insufficient for networks because they only quantify the contribution of each edge's reliability to network reliability. The counting process is a kind of stochastic process that can count the number of edge failures appeared in a time of period, which requires less information than knowing all edge reliabilities. In the context of edge failures subject to a counting process, this paper investigates importance measures for a given binary K -terminal network including n binary edges. This paper develops some formulas to compute the joint failure importance (JFI) and the marginal failure importance (MFI). The MFI quantifies the changes of network failure probability caused by the change of edge state, while the JFI evaluates the interaction effect between two edges regarding network failure probability. Their values, as functions of time t, depend on the probability distribution of the total number of edge failures at time t and the network structure. Additionally, we present a Monte-Carlo algorithm to approximate the values of the MFI and JFI. Finally, a numerical example concerning the road network is provided to demonstrate the computation methods of MFI and JFI, whose edge failures are subject to a saturated nonhomogeneous Poisson process. The numerical results provide further insights for the road network regarding the importance of edges.